Explaining launch spreads on structured bonds - Firla-Cuchra, M (University of Oxford, 2005)
We investigate determinants of launch spreads in European securitization transactions over the last decade. First, we develop a simple, reduced-form pricing model for all issues across different transaction types and test it. We document the critical importance of credit ratings without refinements as the key pricing factors for structured finance securities at launch. Next, we show that other price determinants, such as placement characteristics, are consistently significant in their impact on spreads and delineate the opposing effects of liquidity and market segmentation. Finally, we show that other factors that might directly affect investors' payoffs, such as creditors' rights, exhibit consistent relationships to launch spreads beyond the credit rating. Hence, we conjecture that credit rating agencies systematically differ from investors in their assessment of certain issues' and markets' characteristics.